2021
DOI: 10.1007/s11119-021-09814-x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of artificial intelligence in German agriculture: an application of the technology acceptance model and the theory of planned behavior

Abstract: The use of Artificial Intelligence (AI) in agriculture is expected to yield advantages such as savings in production resources, labor costs, and working hours as well as a reduction in soil compaction. However, the economic and ecological benefits of AI systems for agriculture can only be realized if farmers are willing to use them. This study applies the technology acceptance model (TAM) of Davis (1989) and the theory of planned behavior (TPB) of Ajzen (1991) to investigate which behavioral factors are influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(33 citation statements)
references
References 53 publications
1
30
0
2
Order By: Relevance
“…Another research by Cakirli Akyüz and Theuvsen (2020) from behavioral studies in Turkey on willingness to apply and sustain organic farming practices, demonstrated that the subjective norm is a major driver for organic agriculture adoption and maintenance. While Mohr and Kühl (2021) found that perceived behavioral control (PBC) was the strongest predictor among two constructs, TAM and TPB, in influencing farmers in Germany to accept artificial intelligence in agriculture.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Another research by Cakirli Akyüz and Theuvsen (2020) from behavioral studies in Turkey on willingness to apply and sustain organic farming practices, demonstrated that the subjective norm is a major driver for organic agriculture adoption and maintenance. While Mohr and Kühl (2021) found that perceived behavioral control (PBC) was the strongest predictor among two constructs, TAM and TPB, in influencing farmers in Germany to accept artificial intelligence in agriculture.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Different assumptions should be made for the heterogeneity of influencing factors so as to ensure the accuracy of the model and, thus, scientifically explain farmers’ technology adoption behavior [ 48 ]. With subsequent revisions and extensions by scholars, the theory has been widely applied in the areas of sharing economy, intelligent transportation systems and agricultural technology [ 49 , 50 , 51 , 52 , 53 , 54 ]. Shamsi analyzed the well-being of 3140 academic staff at three Norwegian universities, using technology acceptance theory to delve further into the impact of using online forms of teleconferencing in daily teaching and other tasks on well-being in the context of the global new coronary pneumonia [ 55 ].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Spanaki et al (2021) addressed the issues concerning food security and proposed an AI technique as a solution by adopting a design science methodology [ 31 ]. Mohr & Kühl (2021) investigated the barriers in AI acceptance in agriculture and applied technology acceptance model [ 32 ]. Nevertheless, Mahto et al (2021) used artificial neural network (ANN) to forecast prices of agriculture commodities and compared of performance of their model with ARIMA model for sustainable agriculture [ 33 ].…”
Section: Discussionmentioning
confidence: 99%